2014
DOI: 10.1177/1757975913511133
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, localization and food culture: perceived roles of social and cultural capitals in healthy child feeding practices in Japan

Abstract: Identifying and promoting the social and cultural capital that positively support healthy child feeding practices may be an important component of nutrition education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For many centuries, Japanese people have been taught at school, and at home, how to appreciate food. Although little historical research has been documented around this pervasive practice, one study reported that Japanese mothers taught their children to appreciate food and to eat healthily (17). Appreciation for food is stipulated in the Shokuiku Basic Act (2005), the law pertaining to the education of food and nutrition in Japan (18).…”
Section: Introductionmentioning
confidence: 99%
“…For many centuries, Japanese people have been taught at school, and at home, how to appreciate food. Although little historical research has been documented around this pervasive practice, one study reported that Japanese mothers taught their children to appreciate food and to eat healthily (17). Appreciation for food is stipulated in the Shokuiku Basic Act (2005), the law pertaining to the education of food and nutrition in Japan (18).…”
Section: Introductionmentioning
confidence: 99%
“…Participants of our current study noted the importance of involving children in growing food, as well as serving home-grown food to their families. According to a study in Japan, parents of young children emphasized the importance of home gardening as part of food parenting and feeding practices (9). Benefits of gardening in different settings have been well researched.…”
Section: Discussionmentioning
confidence: 99%
“…To date there is limited information about mindful eating or mindful food parenting practices in different cultures. Past research suggests that the encouragement of mindful eating may be an important element of food parenting and child feeding in some cultures (9,10). Food parenting that focused on traditional food culture may promote healthier eating habits among Hmong, Latino and non-Hispanic white children (10).…”
Section: Introductionmentioning
confidence: 99%
“…For example, there were no significant differences in dietary salt intake according to the number of times soup was consumed per day. Soup, especially miso (fermented soybean paste) soup, was originally an essential part of one's meals in Japan and is a basic form of traditional Japanese cuisine [13] [14]. Dietary salt restriction policies for the past dozen years or so in Japan have focused on the reduction of the frequency of soup intake as one of the most important targets [8].…”
Section: Discussionmentioning
confidence: 99%